Evaluation of the effects on nasal mucociliary clearance of various nasal solutions applied topically in patients with sinusitis - Murat Yasar; Mehmet Yavuz Sutbeyaz; Muhammed Sedat Sakat; Korhan Kilic (Medicine Science, 2018)
Mucociliary clearance (MC) is one of the main defense mechanisms of the nasal respiratory mucosa. The purpose of this study was to determine changes occurring nasal MC in patients with sinusitis, and how medical treatment affects changes in MC, and to identify an appropriate topical solution with positive effects on MC for use in the treatment of sinusitis by examining the effects of various topical solutions on MC. 60 patients diagnosed with rhinosinusitis at the ear, nose and throat clinic were included in this prospective study. Patients were randomly assigned into groups. Group 1 (n:10) received no topical treatment. Group 2 (n:10) was administered with fluticasone propionate, Group 3 (n:10) received mometasone furoate and Group 4 (n:10) received oxymetazoline. Group 5 (n:10) received isotonic sea water for nasal irrigation, while Group 6 (n:10) received isotonic Ringers solution for nasal irrigation. Group 7 represented the control group (non-sinusitis). The saccharin test was used to determine nasal mucociliary clearance times. The saccharin test was performed before and on the 2nd week of treatment in all groups. Basal MCT and 2nd week MCT values were compared in all groups. When measurements performed 20 min and 14 days after administration of topical agents were compared with basal values, mean MCT values at 20 min. and 14 days were shorter in all groups compared to mean basal MCT values. However, the difference between 20-min, 14th day and basal MCT values was only statistically significant in the oxymetazoline and isotonic Ringers solution groups (p [Med-Science 2018; 7(1.000): 1-4]